2007
DOI: 10.1172/jci32738
|View full text |Cite|
|
Sign up to set email alerts
|

Parathyroid hormone inhibits renal phosphate transport by phosphorylation of serine 77 of sodium-hydrogen exchanger regulatory factor–1

Abstract: Parathyroid hormone (PTH), via activation of PKC and/or protein kinase A, inhibits renal proximal tubular phosphate reabsorption by facilitating the internalization of the major sodium-dependent phosphate transporter, Npt2a. Herein, we explore the hypothesis that the effect of PTH is mediated by phosphorylation of serine 77 (S77) of the first PDZ domain of the Npt2a-binding protein sodium-hydrogen exchanger regulatory factor-1 (NHERF-1). Using recombinant polypeptides representing PDZ I, S77 of NHERF-1 is phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 27 publications
8
117
0
Order By: Relevance
“…Ezrin, by virtue of its protein kinase A anchoring capacity, positions the PKA holoenzyme in proximity to the Npt2a-NHERF1-ezrin ternary complex. Upon PTH stimulation and the concomitant production of cAMP, anchored PKA phosphorylates NHERF1 on target serines (38,45). This cascade of events induces the dissociation of Npt2a from the ternary complex, resulting in Npt2a internalization and degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ezrin, by virtue of its protein kinase A anchoring capacity, positions the PKA holoenzyme in proximity to the Npt2a-NHERF1-ezrin ternary complex. Upon PTH stimulation and the concomitant production of cAMP, anchored PKA phosphorylates NHERF1 on target serines (38,45). This cascade of events induces the dissociation of Npt2a from the ternary complex, resulting in Npt2a internalization and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed peptide fragments harboring Ser 77 located in PDZ1, which has been associated with PTHinduced NHERF1 phosphorylation (38), and the linker region between PDZ2 and the EBD, which contains a serine-rich cluster (Fig. 1A), including Ser 290 , which is constitutively phosphor- ylated (39) and has been implicated in PKC-mediated phosphorylation (40,41).…”
Section: Binary Nherf1 Interactions With Npt2a and Ezrin-pthmentioning
confidence: 99%
“…Our previous study (13) showed that activation of atypical PKC (aPKC) led to NF-jB activation and a decrease of PPARc expression. Considering the fact that various hormones, including insulin, angiotensin II, glucagons, parathyroid hormone, endothelin-1, thrombin, and vitamin D3, and high glucose concentration, activate c/nPKC (14)(15)(16)(17)(18)(19), evaluating the role of c/nPKC on gene expression in adipocyte may provide a new understanding of the regulation of insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Neither short term up-or down-regulation seems to involve changes on mRNA levels, suggesting a posttranscriptional control. The nature of this posttranscriptional mechanism has been clarified in the case of the PTH-induced downregulation of NaPi-IIa: PTH administration leads to phosphorylation of NHERF1, an adaptor protein that contributes to stabilize NaPi-IIa at the proximal BBM; phosphorylation of NHERF1 decreases its affinity for NaPi-IIa, resulting in a reduced stability and therefore removal of the cotransporter from the apical membrane (Deliot et al, 2005;Weinman et al, 2007). Whether or not similar protein-protein interaction mechanisms contribute to stabilize the membrane expression of NaPi-IIc and /or NaPi-IIb is unknown.…”
Section: Physiological Pathophysiological and Pharmaceutical Aspectsmentioning
confidence: 99%